#### Answer

$r' = -\theta (2 sin\theta + \theta cos\theta)$

#### Work Step by Step

$r = 4-\theta ^{2}sin\theta $
$r' = 0- (2\theta sin\theta + \theta^{2}cos\theta)$
$r' = -\theta (2 sin\theta + \theta cos\theta)$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$r' = -\theta (2 sin\theta + \theta cos\theta)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.